Cover Picture: (Electroanalysis 1/2014). Issue 1 (January 2014) - Unknown
<x xml:space="preserve">Abstract</x> Electroanalysis publishes research devoted to fundamental as well as practical aspects of electroanalysis. Its scope includes advances in analytical voltammetry and potentiometry, new electrochemical sensors and detection schemes, novel electrode materials, advanced instrumentation, nanoscale electrochemistry, advanced electromaterials, nanobiolectronics, point‐of‐care diagnostics, wearable sensors, and practical applications in diverse fields, thus serving as a bridge between the reasearch laboratory and the routine analytical laboratory.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>